Fiscal Capacity and Poverty Alleviation: A Panel Data Analysis for Yogyakarta Special Province, Indonesia - Sriyana, Jaka (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2015)
This study attempts to analyze the role of fiscal capacity in poverty alleviation in Yogyakarta for the period of 2006-2013. For this purpose, this study uses panel data approach to estimate the empirical model involving four regencies and a city. This research f ound that fixed effects model is the best model to explain the role of fiscal capacity to the poverty rate. Overall, the results present that all independent variables are good predictors for poverty rate model. Based on the complete fixed effects model, the research shows that public spending and fiscal transfer are significant predictors for poverty rate. In contrast, government own revenue has negative impact to poverty rate. These results indicate fiscal capacity in among regencies and city in Yogyakarta has well managed to improve social welfare. This study also reveals that local governments need to improve their public spending as well as to strengthen their frameworks on public services policies.